FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL - Alex Shaw; Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to obtain empirical evidence regarding the factors that influence capital structure which includes asset growth, firm size, profitability, asset structure, liquidity, and non-debt tax shield on the capital structure of manufacturingcompanies listed on the Indonesia Stock Exchange in 2017-2020. The data used in this study is secondary data, with a sample of 70 manufacturing company data and using purposive sampling. In processing the data, this research uses the E-views 10 program. The results obtained from the study show that firm size, profitability, liquidity, and non-debt tax shield have an effect on capital structure, while asset growth and asset structure have no effect on capital structure.